Pretreatment of lignocellulosic biomass from animal manure as a means of enhancing biogas production - Muhammad Nasir, Ismail (Wiley-VCH Verlag, 2015)
Biogas produced from lignocellulosic biomass, e.g. animal manure, has the potential to be a promising renewable energy source. Special emphasis has been placed on animal manure pretreatment in an anaerobic digestion as a means of enhancing biogas yield. Here, we review the existing pretreatment methods of anaerobic digestion with regard to their effects on the conversion of animal manure to biogas. Various methods and their challenges are highlighted. The effects of pretreatment are complex and usually depend on the animal waste characteristics and the method of choice. In general, pretreatment enhances the anaerobic digestion of the lignocellulosic content of the animal manure, by increasing the methane yield in similar operating conditions as those without the pretreatment.